THE EFFECT OF INVENTORY INTENSITY, FIXED ASSET INTENSITY, POLITICAL CONNECTION AND REAL EARNINGS MANAGEMENT ON TAX AVOIDANCE WITH AUDIT COMMITTEE AS ​​A MODERATING - Dolok Saribu, Alfriado Leonard Noprian; Umi Muawanah; Djuni Farhan (Jurnal Akuntansi Trisakti, 2025)
This study aims to analyze the effect of inventory intensity, fixed asset intensity, political connections and real earnings management on tax avoidance with the audit committee as a moderating variable. This type of research is a causal associative research with a moderated regression analysis technique. The population is all mining sector companies as many as 42 companies listed on the Indonesia Stock Exchange with a sample of 27 mining sector companies with a total of 135 company financial data with panel data type. The data analysis method uses moderated linear regression (MRA). The results of the study indicate that inventory intensity has a significant positive effect on tax avoidance, fixed asset intensity does not affect tax avoidance, political connections have a significant positive effect on tax avoidance, real earnings management does not affect tax avoidance, the audit committee strengthens the effect of inventory intensity on tax avoidance, the audit committee cannot moderate the effect of fixed asset intensity on tax avoidance, the audit committee weakens the effect of political connections on tax avoidance and the audit committee cannot moderate the effect of real earnings management on tax avoidance. The results of this study can be a source of decision making for companies related to factors that can cause tax avoidance and as a source of knowledge for management to avoid tax avoidance by analyzing the variables of intensity, fixed assets, political connections and real earnings management and the audit committee as a moderating variable that can minimize tax avoidance.